The Nature-Based Tourism Package. Travel Agent Perspectives - ANUAR, Ahmad Nazrin Aris; SAPARI, Nurul Natasha Syahira; SULAIMAN, Firdaus Chek; HASHİM, Nur Idzhainee; JAİNİ, Norajlin (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.12.6(54).11, 2021)
Travel agent plays a significant role in promoting of tourism and attraction in the country. They will assist the tourists to propose, choose and organize their holiday. They also design the itinerary and provide consultation for the finest suggestion to them. Therefore, this study aims to understand the vacation packages based on the natural area around travel agents in Petaling Jaya, Selangor, Malaysia. The objectives of this study are: i) to identify the factor that influences nature-based tourism package by the travel agent, ii) to determine the characteristic preferred by travel agent toward nature-based tourism package. This study is using a convenient sampling method thru questionnaires as a tool to distributed concerning the travel agent that provides nature-based tourism at the study area. The result shows that most of the travel agents provided a nature-based tourism package to fulfill the demand in the nature-based tourism area. This study may encourage the travel agent to expand their service as a nature-based tourism area provider to realize the demand of their customer.